Sapphirine-bearing Fe-rich granulites in the SW Siberian craton (Angara-Kan block): Implications for Paleoproterozoic ultrahigh-temperature metamorphism - Sukhorukov, V.; Turkina, O.; Tessalina, Svetlana; Talavera, Cristina (Elsevier BV, 2018)
We report here for the first time the occurrence of sapphirine-bearing rocks within the Paleoproterozoic granulite complex of the Angara-Kan block (SW Siberian craton) and provide strong evidence for crustal metamorphism at ultrahigh-temperature (UHT) conditions in this region. The UHT rocks contain sapphirine, high alumina orthopyroxene, orthopyroxene + sillimanite assemblage, mesoperthitic feldspar and pseudomorphoses after osumilite crystals. The peak temperature of metamorphism was estimated using Al 2 O 3 contents in Opx (up to 10 wt%) and the ternary feldspar composition, and falls in a range of 1050–1100 °C. Observed mineral microstructures indicate post-peak cooling of rocks without a considerable decrease in pressure down to a temperature of about 900 °C. Another type of rock related with UHT metamorphism is represented by orthopyroxene-sillimanite gneisses, which recorded a peak temperature of about 950 °C, decreasing down to 900 °C during post-peak stage. The UHT gneisses record microstructural evidence of melt injection and matrix-melt interaction near the peak metamorphic conditions. Sapphirine grains occur in the gneiss with relatively low Mg bulk composition. It is suggested that sapphirine occurs in the Mg-Al-rich domains which have been formed as a result of partial melting and precipitation of Fe-oxides from the melt. High concentrations of Al 2 O 3 in orthopyroxene are the only sign of UHT metamorphism in Fe-rich rock matrix which is not affected by melt. New SHRIMP U-Pb zircon data from two UHT gneisses indicate the presence of two well-defined age peaks at ca. 1.8 and 1.9 Ga from rims and metamorphic grains, and older dates from ca. 1.91 to 3.15 Ga from detrital cores. The prominent feature of the metamorphic zircons is depletion of U with high Th/U ratio up to 6.0. Steep HREE patterns of the metamorphic zircons suggest their growth in the presence of a melt. The metamorphic zircons from the UHT gneiss record a broad range of temperatures between 1000 °C and 810 °C indicating protracted zircon growth from near peak conditions through retrograde stage of PT-path. The growth of the youngest zircons occurred at higher temperature indicating that the UHT metamorphic conditions were reached at 1.78–1.8 Ga. The timespan of the granulite-UHT metamorphic event is near 50 Ma and is limited by intrusions of late leucogranites and charnockites at 1.75–1.73 Ga. Protracted interval of granulite-UHT metamorphism conforms with isobaric cooling P-T path constructed by mineral assemblages.